Epidemiology, evolutionary origin, and malaria‐induced positive selection effects of G6PD‐deficient alleles in Chinese populations. Issue 12 (31st October 2020) - Zheng, Yuzhong; Wang, Junli; Liang, Xueyan; Huang, Huiying; Ma, Yanbo; Lin, Liyun; Wang, Chunfang; Zhan, Xiaofen; Yang, Liye; Zha, Guangcai; Yang, Peikui; Zou, Xianghui; et al.
Abstract: Background: Although glucose‐6‐phosphate dehydrogenase ( G6PD ) deficiency is the most common inherited disorder in the Chinese population, there is scarce evidence regarding the epidemiology, evolutionary origin, and malaria‐induced positive selection effects of G6PD ‐deficient alleles in various Chinese ethnic populations. Methods: We performed a large population‐based screening ( n = 15, 690) to examine the impact of selection on human nucleotide diversity and to infer the evolutionary history of the most common deficiency alleles in Chinese populations. Results: The frequencies of G6PD deficiency ranged from 0% to 11.6% in 12 Chinese ethnic populations. A frequency map based on geographic information showed that G6PD deficiency was highly correlated with historical malaria prevalence in China and was affected by altitude and latitude. The five most frequently occurring G6PD gene variants were NM_001042351.3:c.1376G>T, NM_001042351.3:c.1388G>A, NM_001042351.3:c.95A>G, NM_001042351.3:c.1311T>C, and NM_001042351.3:c.1024C>T, which were distributed with ethnic features. A pathogenic but rarely reported variant site (NM_001042351.3:c.448G>A) was identified in this study. Bioinformatic analysis revealed a strong and recent positive selection targeting the NM_001042351.3:c.1376G>T allele that originated in the past 3125 to 3750 years and another selection targeting the NM_001042351.3:c.1388G>A allele that originated in the past 5000 to 6000 years. Additionally, both alleles originated from a single ancestor. Conclusion: These results indicate that malaria has had a major impact on the Chinese genome since the introduction of rice agriculture. Abstract : Strong and recent positive selection have targeted on the c.1376 G>T allele with the past 3125–3750 years and c.1388 G>A allele with the past 5000–6000 years. Malaria has had a major impact on Chinese genome since the introduction of rice agriculture.